Regulation of Gene Expression in Physiological Changes of Wheat Under Drought Stress - Danishiar, Sayeed Qadir (Journal of Natural Sciences – Kabul University, 2021)
Wheat (Triticum aestivum), the staple food of 89 countries, including Afghanistan, is expected to decline by 40% due to extreme heat and dry conditions worldwide. According to the Office of Global Analysis, wheat imports to Afghanistan increased from 2,700 tons to 3,700 tons from 2016 to 2019, highlighting the need for further research on wheat under drought conditions. Drought stress has destructive effects on germination, stems, shrubs, flowers, and spikes, while elongated roots, wax layers, and stomatal pores (which control CO2 intake during photosynthesis) play a crucial role in water retention and storage. Drought increases the requirement for adenosine triphosphate (ATP), but Reactive Oxygen Species (ROS) also increase under drought conditions, leading to plant damage. In wheat, 309 genes, including WRKY transcription factors and the Ethylene-responsive element binding factor-associated Amphiphilic Repression (EAR) motif, were detected in response to drought stresses.